A high-ductility cement-based composite material and preparation method thereof

By using silica fume and calcium silicate to replace fly ash in high-ductile cement-based composite materials, and combining modified fibers and polyimide aerogel composite acrylate resin, the problems of brittleness, crack resistance and seismic resistance of traditional building materials are solved, and the material's quality stability, mechanical properties and thermal insulation properties are improved.

CN119569398BActive Publication Date: 2025-04-22HOMOGEN NEW QUALITY (XIAN) NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510115692.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-22
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

Traditional building materials have problems of brittleness, crack resistance and seismic resistance in performance. At the same time, the instability of fly ash affects the quality stability of high-ductile mortars, and insufficient insulation performance leads to excessive energy consumption.

Method used

Using a highly ductile cement-based composite material without adding fly ash, by adding fume and calcium silicate to the cement as a substitute, combining modified PVA fibers and PE fibers, polyimide aerogel composite acrylate resin is used to modify PVA fibers to improve the ductility and mechanical properties of the material, and the thermal conductivity is reduced through the nanopore structure of the polyimide aerogel to improve the insulation performance.

Benefits of technology

It has achieved the improvement of the quality stability and mechanical properties of high-ductility cement matrix composite materials, and has good energy-saving and thermal insulation functions, solving the shortcomings of traditional building materials in terms of performance and thermal insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to building materials, and specifically discloses a high-ductility cement-based composite material and a preparation method thereof, wherein the cement-based composite material comprises the following raw materials in parts by weight: cement, water, admixture, PE fiber, modified PVA fiber, sand, hollow glass microspheres, silica fume, calcium silicate, and expanded perlite; wherein the modified PVA fiber is prepared by composite modification of polyimide aerogel composite acrylate resin and epoxy resin; and the preparation method thereof comprises the following steps: mixing cement, silica fume, sand, calcium silicate and expanded perlite and then adding PE fiber to prepare a dry-mixed mixture; mixing the admixture with water to prepare a mixture, then adding the modified PVA fiber, stirring evenly and then adding the dry-mixed mixture, stirring evenly to prepare a high-ductility cement-based composite material. The present application has the characteristics of not adding fly ash to ensure product quality stability, and also has good mechanical properties and ductility, and at the same time has energy-saving and heat-insulating functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building materials, and more specifically, to a high-ductility cement-based composite material and a preparation method thereof. Background Art

[0002] With the rapid development of the construction industry, the requirements for building materials are getting higher and higher. Traditional building materials often have many deficiencies in performance, such as brittleness, poor crack resistance and earthquake resistance, which seriously affect the service life and safety of buildings.

[0003] High-ductility cement-based material is a new type of building material with high ductility and strength. It improves the mechanical properties and durability of cement by adding special admixtures and fiber reinforcement materials to ordinary cement. It is widely used in construction, roads, bridges, tunnels and other fields.

[0004] The high-ductility mortar in the related technology is based on cement, fly ash, silica fume, sand and water. PVA fiber is added to improve the toughness and ductility of the mortar, obtaining a building material with high strength, high ductility, high durability and high damage resistance, which solves the problems of brittleness, crack resistance and poor seismic resistance of existing mortars.

[0005] However, the fly ash added in the above scheme, as solid waste from power plants, is often unstable in performance and has varying quality in different regions, which seriously affects the quality stability of high-ductility mortar. Traditional building materials are often insufficient in terms of thermal insulation, resulting in excessive energy consumption and being unfavorable to sustainable development.

[0006] Therefore, developing a new composite material that does not add fly ash to ensure the stability of product quality while ensuring its mechanical properties and having energy-saving and thermal insulation functions is of great significance to promoting the sustainable development of the construction industry. Summary of the invention

[0007] In order to ensure the stability of product quality, have good mechanical properties and ductility without adding fly ash, and have energy-saving and heat-insulating functions, the present application provides a high-ductility cement-based composite material and a preparation method thereof.

[0008] In a first aspect, the present application provides a high-ductility cement-based composite material, which adopts the following technical solution:

[0009] An energy-saving, heat-insulating, high-ductility cement-based composite material comprising the following raw materials in parts by weight:

[0010] 90-120 parts of cement, 50-60 parts of water, 0.3-0.8 parts of admixture, 5-10 parts of PE fiber, 5-10 parts of modified PVA fiber, 50-70 parts of sand, 8-15 parts of hollow glass microspheres, 10-20 parts of silica fume, 8-15 parts of calcium silicate, 10-15 parts of expanded perlite;

[0011] The modified PVA fiber is prepared by composite modification of polyimide aerogel, acrylate resin and epoxy resin.

[0012] By adopting the above technical scheme, cement is used as the main material in this application, and calcium silicate and silica fume are added instead of fly ash. Silica fume can significantly improve the strength and durability of concrete, and is especially suitable for high-performance concrete. Calcium silicate, as a cement admixture, can react with residual calcium hydroxide in cement to form a new hardening product, thereby enhancing the hardness and compressive strength of cement. In this application, silica fume and calcium silicate are used as effective substitutes for fly ash to improve the overall performance of cement-based composite materials.

[0013] In addition, the raw materials of the present application are added with PE fibers and PVA fibers modified by polyimide aerogel composite acrylate resin and epoxy resin. The addition of PVA fibers can improve the brittleness of cement mortar and enhance its toughness, so that concrete can better absorb kinetic energy when subjected to force and improve impact resistance. The epoxy resin modification utilizes the epoxy groups in the epoxy resin to react with the hydroxyl groups in the PVA, thereby enhancing the intermolecular force of the PVA fibers and improving their ductility and tensile properties. The polyimide aerogel itself, as a new type of aerogel material, has the characteristics of high porosity and low thermal conductivity. Point, when it is added to cement mortar, it can effectively reduce the thermal conductivity of cement mortar, thereby improving its thermal insulation performance, and the nanoporous structure of polyimide aerogel is conducive to the scattering and reflection of heat, further enhancing its thermal insulation effect, and polyimide aerogel has excellent mechanical flexibility, combined with the high strength and high modulus characteristics of acrylic resin to enhance the mechanical properties of PVA fiber such as ductility and strength, and the epoxy resin and acrylic copolymer can form an interpenetrating network structure, which has a synergistic effect and further improves the ductility and mechanical properties of PVA fiber.

[0014] Finally, the cement-based composite material prepared by combining the modified PVA fiber and PE fiber in this application has excellent ductility and mechanical properties, and no fly ash is added to the raw material system, thereby ensuring the quality stability of the product. The polyimide aerogel-modified PVA fiber is then dispersed in the cement composite material system, which has better resistance to external deformation, thereby maintaining the overall integrity and stability of the material, and its pore structure is also better retained, which has a better thermal insulation effect, thereby obtaining a high-ductility cement-based composite material without adding fly ash with energy-saving and thermal insulation effects.

[0015] Optionally, the modified PVA fiber is prepared by the following method:

[0016] The PVA fiber is mixed and dispersed with a mixed solution of water and acetone, and then a polyimide aerogel composite acrylate resin is added and stirred and dispersed, and then ammonia water and sodium stearate are added and the temperature is raised to 45-55°C, and then epoxy resin is added and stirred for 30-40 minutes, and then the mixture is cooled and dried to obtain a dried product, and then the dried product is ultrasonically dispersed in a hydroxypropyl β-cyclodextrin solution and centrifugally dried to remove water to obtain a modified PVA fiber.

[0017] By adopting the above technical scheme, in the present application, PVA fibers are first added to a mixed solution of water and acetone for dissolution and dispersion, and then a polyimide aerogel composite acrylate resin is added. Under the alkaline condition of ammonia water, the polyimide aerogel composite acrylate resin forms a chemical reaction with the hydroxyl groups of the PVA fibers, and a chemical bond is also formed between the epoxy resin and the PVA fibers, thereby achieving a composite modification of the PVA fibers and significantly improving their ductility and mechanical properties. The epoxy resin and the polyimide aerogel composite acrylate resin form a cross-network structure, which significantly improves the ductility and mechanical properties of the PVA fibers. Moreover, the addition of the polyimide aerogel significantly improves the thermal insulation properties of the cement composite material, and the addition of sodium stearate improves the uniform dispersion of the PVA fibers, the polyimide aerogel composite acrylate resin and the epoxy resin, thereby improving the modification effect.

[0018] Optionally, during the preparation of the modified PVA fiber, each raw material is added according to the following weight parts:

[0019] 15-20 parts of PVA fiber, 10-20 parts of water, 10-20 parts of acetone, 5-10 parts of polyimide aerogel composite acrylate resin, 3-5 parts of ammonia water, 0.5-1 part of sodium stearate, 3-6 parts of epoxy resin;

[0020] The amount of hydroxypropyl β-cyclodextrin solution added is 3-5 times the mass of the dried product, and the mass concentration of the hydroxypropyl β-cyclodextrin solution is 35-50wt%.

[0021] By adopting the above technical scheme, in this application, epoxy resin and polyimide aerogel composite acrylate resin are used to compositely modify PVA fibers and then ultrasonically dispersed in a hydroxypropyl β-cyclodextrin solution. Hydroxypropyl β-cyclodextrin has a lipophilic cavity and a hydrophilic shell. Its special structure can achieve the coating of the lipophilic part of the modified PVA fiber, thereby improving its uniform dispersion in the cement mortar system and improving its overall performance.

[0022] Optionally, the polyimide aerogel composite acrylate resin is prepared by the following method:

[0023] 1) Add (1 / 4-1 / 2) of the total amount of acrylate monomer, mix with sodium styrene sulfonate and solvent A, add polyimide aerogel, impregnate and dry to obtain pretreated aerogel;

[0024] 2) The remaining acrylate monomer, dimethylaminoethyl acrylate, 2-acrylamide-2-methylpropane sulfonic acid, propylene glycol monoallyl ether, initiator, crosslinker and stabilizer, toluene and solvent B are mixed to obtain a reaction solution, and then the pretreated aerogel prepared in step 1) is added, and the mixture is polymerized at 80-90° C. for 3-5 hours, and then the mixture is heated to 110-120° C. and reacted for 1-2 hours to obtain a polyimide aerogel composite acrylate resin.

[0025] By adopting the above technical scheme, in the present application, part of the acrylic acid monomer, sodium styrene sulfonate and solvent are first mixed with the polyimide aerogel and then dried, so that the acrylic acid monomer and the styrene solution are coated on the surface of the polyimide aerogel, and then mixed with the reaction solution. Under the action of the initiator, the acrylic acid monomer and monomers such as propylene glycol monoallyl ether are in situ polymerized on the surface and inside of the polyimide aerogel to form an acrylate resin. The introduction of sodium styrene sulfonate on the surface of the pretreated aerogel allows the sulfonic acid group to react with the hydroxyl group in the propylene glycol monoallyl ether in the reaction solution, thereby achieving the reaction. The monomers in the solution are copolymerized with the monomers on the surface of the aerogel to achieve in-situ polymerization with the aerogel as the skeleton structure to obtain an acrylate copolymer. The addition of toluene in the reaction solution realizes the establishment of a pore structure for the acrylate copolymer, and finally an amino-modified acrylic resin is obtained with a polyimide aerogel as the skeleton structure and in-situ polymerization. The polyimide aerogel itself has the characteristics of high specific surface area and a large number of micropores and hollow structures. The acrylic resin with a pore structure formed by the addition of toluene porogen during in-situ polymerization has better thermal insulation performance and plays a better role in enhancing mechanical properties.

[0026] Optionally, the acrylic acid ester monomer is selected from one or more of methyl methacrylate, ethyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, and lauryl methacrylate;

[0027] The initiator is selected from one or both of benzoyl peroxide and azobisisobutyronitrile;

[0028] The cross-linking agent is selected from one or both of ethylene glycol dimethacrylate and trimethylolpropane triacrylate;

[0029] The stabilizer is selected from one or more of polyvinyl pyrrolidone and polyethylene glycol;

[0030] In step 1), the solvent A is selected from methanol and water in a mass ratio of 1: (1.2-1.3);

[0031] The solvent B in step 2) is a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:(0.1-0.2).

[0032] By adopting the above technical scheme, the introduction of amino functional groups in dimethylaminoethyl acrylate in the present application introduces amino groups on the main molecular chain, so that it can form a chemical bond with epoxy resin and PVA fiber to form a three-dimensional network structure, thereby improving the mechanical properties and ductility of PVA fiber. The introduction of sulfonic acid groups helps to improve the solubility of polyimide aerogel composite acrylate in water, improve its modification effect with PVA fiber and ultimately its compatibility and dispersibility in cement composite materials, thereby improving the overall performance.

[0033] Optionally, when preparing the polyimide aerogel composite acrylate resin, each raw material is added according to the following weight parts:

[0034] 30-50 parts of acrylate monomer, 5-8 parts of sodium styrene sulfonate, 40-50 parts of solvent A, 20-30 parts of polyimide aerogel, 30-40 parts of acrylate monomer, 10-20 parts of dimethylaminoethyl acrylate, 8-15 parts of 2-acrylamide-2-methylpropane sulfonic acid, 10-20 parts of propylene glycol monoallyl ether, 3-5 parts of initiator, 3-5 parts of crosslinking agent, 3-5 parts of stabilizer, 5-10 parts of toluene, 60-70 parts of solvent B.

[0035] Optionally, the PE fiber is added after the following pretreatment:

[0036] 1) Melt and blend the silica gel particles and EPDM rubber particles, add dioctyl phthalate, and mix them by internal kneading to obtain a blend;

[0037] 2) After the PE fiber is melted, it is mixed with the blend obtained in step 1) and the carbon nanotubes and then subjected to composite spinning to obtain pretreated PE fiber and then added.

[0038] By adopting the above technical scheme, in this application, silica gel particles and EPDM rubber particles are mixed with PE fibers for melt spinning. The addition of silica gel particles and EPDM further improves the toughness of PE fibers and further improves their ductility, while the addition of carbon nanotubes plays a reinforcing role. Finally, the addition of PE fibers after the above pretreatment plays a role in improving better ductility and strength mechanical properties.

[0039] Optionally, during the pretreatment of the PE fiber, the mass ratio of silica gel particles to EPDM rubber is 1:(2-3), the amount of dioctyl phthalate added is 1-3wt% of the silica gel particles, the mass ratio of PE fiber to the blend is 1:(0.1-0.2), and the amount of carbon nanotubes added is 1-3wt% of the PE fiber.

[0040] By adopting the above technical solution, the addition of a small amount of carbon nanotubes can not only improve the mechanical properties, but also have little effect on the thermal insulation effect, so that the comprehensive performance of the mechanical properties and thermal insulation properties of the obtained cement composite material is better.

[0041] Optionally, the pretreated PE fiber has a length of 5-10 mm and a diameter of 30-40 μm.

[0042] By adopting the above technical solution and selecting the above-mentioned scale of pretreated PE fibers, the ductility can be improved better.

[0043] In a second aspect, the present application provides a method for preparing a high-ductility cement-based composite material, using the following technical solution:

[0044] A method for preparing an energy-saving, heat-insulating, high-ductility cement-based composite material comprises the following steps:

[0045] The cement, silica fume, sand, hollow glass microspheres, calcium silicate and expanded perlite are mixed and then PE fibers are added to prepare a dry mix;

[0046] The admixture is mixed with water to obtain a mixture, and then the modified PVA fiber is added, stirred evenly, and then the dry-mixed mixture is added, and stirred evenly to obtain an energy-saving, heat-insulating, and high-ductility cement-based composite material.

[0047] By adopting the above technical solution, the preparation method provided by the present application is simple and convenient and easy to realize industrialization.

[0048] In summary, this application has the following beneficial effects:

[0049] 1. In this application, cement is used as the main material, and calcium silicate and silica fume are added to replace fly ash. Silica fume can significantly improve the strength and durability of concrete, and is especially suitable for high-performance concrete. Calcium silicate, as a cement admixture, can react with residual calcium hydroxide in cement to form a new hardening product, thereby enhancing the hardness and compressive strength of cement. In this application, silica fume and calcium silicate are used as effective substitutes for fly ash to improve the overall performance of cement-based composite materials.

[0050] 2. The cement-based composite material prepared by combining the modified PVA fiber and PE fiber in the present application has excellent ductility and mechanical properties, and no fly ash is added to the raw material system, thereby ensuring the quality stability of the product. The polyimide aerogel-modified PVA fiber is then dispersed in the cement composite material system, which has better resistance to external deformation, thereby maintaining the overall integrity and stability of the material, and its pore structure is also better retained, which has a better thermal insulation effect, thereby obtaining a high-ductility cement-based composite material without adding fly ash with energy-saving and thermal insulation effects. DETAILED DESCRIPTION

[0051] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0052] In the following examples, PO52.5R ordinary Portland cement is used as cement; medium sand with a particle size of 0.35-0.40 mm and fine sand with a particle size of 0.25-0.30 mm in a mass ratio of 1:2 are used as sand; and polycarboxylate water reducer model CP1200 of Nanjing Xinyi Synthetic Technology Co., Ltd. is used as admixture;

[0053] The silicone particles are thermoplastic silicone particles from Dongguan Jinsuyan Plastic Technology Co., Ltd.;

[0054] The EPDM rubber used is the EPDM terpolymer EPDM with the product number EPDM-3092 from Dongguan Xinrun Trading Co., Ltd.

[0055] The length of the PVA fiber in the following preparation examples and embodiments is 5-10 mm, the diameter is 30-40 μm, and the length of the PE fiber is 6-12 mm, the diameter is 30-40 μm.

[0056] In the following preparation examples, the epoxy resin used is E44 epoxy resin.

[0057] The following preparation example is a preparation example of modified PVA fiber:

[0058] Preparation Example 1

[0059] A method for preparing a modified PVA fiber comprises the following steps:

[0060] S1, preparing polyimide aerogel composite acrylate resin, taking polyimide aerogel composite acrylate resin as a benchmark, specifically comprising the following steps:

[0061] 1) Mix 15 kg of acrylate monomer, 6 kg of sodium styrene sulfonate and 45 kg of solvent A, add 25 kg of polyimide aerogel, impregnate and dry to obtain pretreated aerogel;

[0062] 2) 35 kg of acrylate monomer, 15 kg of dimethylaminoethyl acrylate, 10 kg of 2-acrylamide-2-methylpropane sulfonic acid, 10 kg of propylene glycol monoallyl ether, 4 kg of initiator, 4 kg of cross-linking agent, 4 kg of stabilizer, 4 kg of toluene and 65 kg of solvent B were mixed to obtain a reaction solution, and then the pretreated aerogel prepared in step 1) was added, and the mixture was polymerized at 85° C. for 4 hours, and then heated to 115° C. for reaction for 1.5 hours to obtain a polyimide aerogel composite acrylate resin;

[0063] The solvent A is selected from methanol and water in a mass ratio of 1:1.2, the solvent B is selected from a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:0.1, the acrylate monomer is selected from methyl methacrylate and ethyl acrylate in a mass ratio of 1:1, the initiator is selected from benzoyl peroxide, the crosslinker is selected from ethylene glycol dimethacrylate, and the stabilizer is selected from polyvinyl pyrrolidone;

[0064] S2, 18kg of PVA fiber was mixed and dispersed with a mixed solution of 15kg of water and 15kg of acetone, and then 8kg of the polyimide aerogel composite acrylate resin prepared in step S1 was added and stirred and dispersed, 4kg of ammonia water containing 25% ammonia and 0.6kg of sodium stearate were added, and the temperature was raised to 50°C, and then 5kg of epoxy resin was added and stirred for 35 minutes, and then dried after cooling to obtain a dried product;

[0065] S3. The dried product is then ultrasonically dispersed in a hydroxypropyl β-cyclodextrin solution and centrifugally dried to remove water. The amount of hydroxypropyl β-cyclodextrin solution added is 4 times the mass of the dried product, and the mass concentration of the hydroxypropyl β-cyclodextrin solution is 42wt%, to obtain modified PVA fiber.

[0066] Preparation Example 2

[0067] A method for preparing a modified PVA fiber comprises the following steps:

[0068] S1, preparing polyimide aerogel composite acrylate resin, taking polyimide aerogel composite acrylate resin as a benchmark, specifically comprising the following steps:

[0069] 1) Mix 10 kg of acrylate monomer, 5 kg of sodium styrene sulfonate and 40 kg of solvent A, add 20 kg of polyimide aerogel, impregnate and dry to obtain pretreated aerogel;

[0070] 2) 30 kg of acrylate monomer, 10 kg of dimethylaminoethyl acrylate, 8 kg of 2-acrylamide-2-methylpropane sulfonic acid, 8 kg of propylene glycol monoallyl ether, 3 kg of initiator, 3 kg of crosslinker, 3 kg of stabilizer, 3 kg of toluene and 60 kg of solvent B were mixed to obtain a reaction solution, and then the pretreated aerogel prepared in step 1) was added, and the mixture was polymerized at 80° C. for 5 h, and then heated to 110° C. for reaction for 1 h to obtain a polyimide aerogel composite acrylate resin;

[0071] The solvent A is selected from methanol and water in a mass ratio of 1:1.2, the solvent B is selected from a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:0.1, the acrylate monomer is selected from isobutyl acrylate, the initiator is selected from azobisisobutyronitrile, the crosslinking agent is selected from trimethylolpropane triacrylate, and the stabilizer is selected from polyethylene glycol;

[0072] S2, 15kg of PVA fiber was mixed and dispersed with a mixed solution of 10kg of water and 10kg of acetone, and then 5kg of the polyimide aerogel composite acrylate resin prepared in step S1 was added and stirred and dispersed, 3kg of ammonia water containing 25% ammonia and 0.5kg of sodium stearate were added, and the temperature was raised to 45°C, and then 3kg of epoxy resin was added and stirred for 30min, and then dried after cooling to obtain a dried product;

[0073] S3. The dried product is then ultrasonically dispersed in a hydroxypropyl β-cyclodextrin solution and centrifugally dried to remove water. The amount of hydroxypropyl β-cyclodextrin solution added is 3-5 times the mass of the dried product, and the mass concentration of the hydroxypropyl β-cyclodextrin solution is 35wt%, to obtain modified PVA fiber.

[0074] Preparation Example 3

[0075] A method for preparing a modified PVA fiber comprises the following steps:

[0076] S1, preparing polyimide aerogel composite acrylate resin, taking polyimide aerogel composite acrylate resin as a benchmark, specifically comprising the following steps:

[0077] 1) Mix 20 kg of acrylate monomer, 8 kg of sodium styrene sulfonate and 50 kg of solvent A, add 30 kg of polyimide aerogel, impregnate and dry to obtain pretreated aerogel;

[0078] 2) 40 kg of acrylate monomer, 20 kg of dimethylaminoethyl acrylate, 15 kg of 2-acrylamide-2-methylpropane sulfonic acid, 15 kg of propylene glycol monoallyl ether, 5 kg of initiator, 5 kg of crosslinker, 5 kg of stabilizer, 5 kg of toluene and 70 kg of solvent B were mixed to obtain a reaction solution, and then the pretreated aerogel prepared in step 1) was added, and the mixture was polymerized at 90° C. for 3 h, and then heated to 120° C. for reaction for 1 h to obtain a polyimide aerogel composite acrylate resin;

[0079] The solvent A is selected from methanol and water in a mass ratio of 1:1.3, the solvent B is selected from a mixture of water and sodium dodecyl sulfate in a mass ratio of 1:0.2, the acrylate monomer is selected from lauryl methacrylate, the initiator is selected from benzoyl peroxide, the crosslinker is selected from ethylene glycol dimethacrylate, and the stabilizer is selected from polyvinyl pyrrolidone;

[0080] S2, 20kg of PVA fiber was mixed and dispersed with a mixed solution of 20kg of water and 20kg of acetone, and then 10kg of the polyimide aerogel composite acrylate resin prepared in step S1 was added and stirred and dispersed, 5kg of ammonia water containing 25% ammonia and 1kg of sodium stearate were added, and the temperature was raised to 55°C, and then 6kg of epoxy resin was added and stirred for 40min, and then dried after cooling to obtain a dried product;

[0081] S3. The dried product is then ultrasonically dispersed in a hydroxypropyl β-cyclodextrin solution and centrifugally dried to remove water. The amount of hydroxypropyl β-cyclodextrin solution added is 5 times the mass of the dried product, and the mass concentration of the hydroxypropyl β-cyclodextrin solution is 50wt%, to obtain modified PVA fiber.

[0082] Preparation Example 4

[0083] A method for preparing modified PVA fiber is carried out according to the method in Preparation Example 1, except that step S3 is not performed, and the dried product obtained in step S2 is directly used as the modified PVA fiber.

[0084] Preparation Example 5

[0085] A method for preparing modified PVA fiber is carried out according to the method in Preparation Example 1, except that dimethylaminoethyl acrylate is not added in step 2) in step S1.

[0086] Preparation Example 6

[0087] A method for preparing modified PVA fiber is carried out according to the method in Preparation Example 1, except that sodium styrene sulfonate and 2-acrylamide-2-methylpropane sulfonic acid are not added in step S1.

[0088] Comparative Preparation Example 1

[0089] A method for preparing modified PVA fiber is carried out according to the method in Preparation Example 1, except that the polyimide aerogel composite acrylate resin in step S2 is directly replaced in equal amounts by a mixture of polyimide aerogel and acrylic resin (methacrylic resin with a brand number of 901 produced by Langfang Hongdong Environmental Protection Technology Co., Ltd.) in a mass ratio of 1:2.

[0090] Comparative Preparation Example 2

[0091] A method for preparing modified PVA fiber is carried out according to the method in Preparation Example 1, except that the polyimide aerogel composite acrylate resin in step S2 is directly replaced by an acrylic resin (methacrylic resin with a brand number of 901 produced by Langfang Hongdong Environmental Protection Technology Co., Ltd.) in an equal amount.

[0092] Comparative Preparation Example 3

[0093] A method for preparing modified PVA fiber is carried out according to the method in Preparation Example 1, except that no polyimide aerogel is added in step S1 1).

[0094] Comparative Preparation Example 4

[0095] A method for preparing modified PVA fiber is carried out according to the method in Preparation Example 1, except that no polyimide aerogel composite acrylate resin is added in step S2.

[0096] Example 1

[0097] A method for preparing a high-ductility cement-based composite material comprises the following steps:

[0098] 100 kg of cement, 15 kg of silica fume, 60 kg of sand, 10 kg of hollow glass microspheres, 15 kg of calcium silicate and 12 kg of expanded perlite were mixed and then 8 kg of PE fiber was added to prepare a dry mix;

[0099] 0.5 kg of polycarboxylate water-reducing agent as an admixture was mixed with 55 kg of water to prepare a mixture, and then 8 kg of the modified PVA fiber prepared in Preparation Example 1 was added, mixed and stirred for 15 minutes, and then added to the dry mixed mixture, and stirred and mixed for 20 minutes to obtain an energy-saving, heat-insulating and high-ductility cement-based composite material.

[0100] Example 2

[0101] A method for preparing a high-ductility cement-based composite material comprises the following steps:

[0102] 90 kg of cement, 10 kg of silica fume, 50 kg of sand, 8 kg of hollow glass microspheres, 10 kg of calcium silicate and 10 kg of expanded perlite were mixed and then 5 kg of PE fiber was added to prepare a dry mix;

[0103] 0.3 kg of polycarboxylate water-reducing agent as an admixture was mixed with 50 kg of water to prepare a mixture, and then 5 kg of the modified PVA fiber prepared in Preparation Example 2 was added, mixed and stirred for 15 minutes, and then added to the dry mixed mixture, and stirred and mixed for 20 minutes to obtain an energy-saving, heat-insulating and highly ductile cement-based composite material.

[0104] Example 3

[0105] A method for preparing a high-ductility cement-based composite material comprises the following steps:

[0106] 120 kg of cement, 20 kg of silica fume, 70 kg of sand, 15 kg of hollow glass microspheres, 20 kg of calcium silicate and 15 kg of expanded perlite were mixed and then 10 kg of PE fiber was added to prepare a dry mix;

[0107] 0.8 kg of polycarboxylate water-reducing agent as an admixture was mixed with 60 kg of water to prepare a mixture, and then 10 kg of the modified PVA fiber prepared in Preparation Example 3 was added, mixed and stirred for 15 minutes, and then added to the dry mixed mixture, and stirred and mixed for 20 minutes to obtain an energy-saving, heat-insulating, and highly ductile cement-based composite material.

[0108] Embodiment 4-6

[0109] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that the modified PVA fibers are the modified PVA fibers prepared in Preparation Examples 4-6, respectively.

[0110] Example 7

[0111] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that 8 kg of PE fibers added to the cement are added after the following pretreatment:

[0112] 1) Melt and blend the silica gel particles and EPDM rubber particles in a mass ratio of 1:2.5, add dioctyl phthalate, and mix them by internal kneading to prepare a blend. The amount of dioctyl phthalate added is 2wt% of the silica gel particles.

[0113] 2) After the PE fiber is melted, it is mixed with the blend obtained in step 1) and the carbon nanotubes and melt-spun to obtain pretreated PE fibers with a length of 5-10 mm and a diameter of 30-40 μm. The added mass ratio of PE fiber to the blend is 1:0.15, and the amount of carbon nanotubes added is 2 wt% of the PE fiber.

[0114] Example 8

[0115] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that 8 kg of PE fibers added to the cement are added after the following pretreatment:

[0116] 1) Melt and blend silica gel particles and EPDM rubber particles in a mass ratio of 1:2, add dioctyl phthalate, and mix by banburying to prepare a blend, wherein the amount of dioctyl phthalate added is 1wt% of the silica gel particles;

[0117] 2) After the PE fiber is melted, it is mixed with the blend obtained in step 1) and the carbon nanotubes and then melt-spun to obtain pretreated PE fibers with a length of 5-10 mm and a diameter of 30-40 μm. The added mass ratio of PE fiber to the blend is 1:0.1, and the amount of carbon nanotubes added is 1wt% of the PE fiber.

[0118] Example 9

[0119] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that 8 kg of PE fibers added to the cement are added after the following pretreatment:

[0120] 1) Melt and blend silica gel particles and EPDM rubber particles in a mass ratio of 1:3, add dioctyl phthalate, and mix by banburying to prepare a blend, wherein the amount of dioctyl phthalate added is 3wt% of the silica gel particles;

[0121] 2) After the PE fiber is melted, it is mixed with the blend obtained in step 1) and the carbon nanotubes and then melt-spun to obtain pretreated PE fibers with a length of 5-10 mm and a diameter of 30-40 μm. The added mass ratio of PE fiber to the blend is 1:0.2, and the added amount of carbon nanotubes is 3wt% of the PE fiber.

[0122] Example 10

[0123] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that 8 kg of PE fibers added to the cement are added after the following pretreatment:

[0124] Silica gel particles and EPDM rubber particles are mixed in a mass ratio of 1:3, and then mixed with a mixture of water and polyvinyl alcohol to obtain an impregnation solution, the amount of water added is 5 times the mass of the silica gel rubber, the amount of polyvinyl alcohol added is 30wt% of the water, and then PE fiber is added and immersed for 40 minutes, then filtered and dried, and the amount of impregnation solution added is 3 times the mass of the PE fiber to obtain pretreated PE fiber.

[0125] Comparative Examples 1-4

[0126] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that the modified PVA fibers are the modified PVA fibers prepared in Comparative Preparation Examples 1-4, respectively.

[0127] Comparative Example 5

[0128] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that no modified PVA fiber is added to the raw material.

[0129] Comparative Example 6

[0130] A method for preparing a high-ductility cement-based composite material is carried out according to the method in Example 1, except that no calcium silicate is added to the raw materials.

[0131] Performance Testing

[0132] The cement-based composite material, that is, cement mortar, prepared in the examples and comparative examples of the present application was subjected to an ultimate tensile value test according to JC / T 2461-2018 "Test Method for Mechanical Properties of High Ductility Fiber Reinforced Cement-Based Composite Materials" to characterize its ductility properties, and then the prepared cement mortar was made into a standard cubic test block of 100mm×100mm×100mm, and its compressive strength was tested after standard curing for 28 days. In addition, the thermal conductivity was tested according to GB / T 20473-2021 "Building Thermal Insulation Mortar", and the test results are shown in Table 1 below.

[0133] Table 1:

[0134]

[0135] The ultimate tensile value is greater than 0.5%, which means that it has good ductility. Combined with the test results in Table 1 above, the cement mortar prepared in this application has excellent ductility, mechanical properties and thermal insulation properties. Combined with the test results of Example 1 and Example 4, when preparing the modified PVA fiber, when it is not finally dispersed in the hydroxypropyl β-cyclodextrin solution, its overall performance is reduced. It may be that the dispersion performance of the modified PVA fiber in the cement mortar is reduced. Combined with the test results of Example 5 and Example 6, when preparing the polyimide aerogel composite acrylate resin, when dimethylaminoethyl acrylate or sodium styrene sulfonate and 2-acrylamide-2-methylpropane sulfonic acid are not added to the monomer raw materials, its performance is also reduced. This is because the introduction of its functional group improves the dispersibility and compatibility of the modified PVA fiber with the cement mortar.

[0136] Referring to the test results of Example 1 and Examples 7-9, when the PE fiber is added after pretreatment, its comprehensive performance is further improved. Combined with the test results of Example 10, the PVA is physically bonded to the silica gel particles during pretreatment, and its performance is significantly reduced compared to when it is added after melt spinning in Example 7.

[0137] Combined with the test results of Example 1 and Comparative Example 1, when acrylic resin and polyimide aerogel are directly added for modification during PVA fiber modification, compared with the modification after composite in-situ polymerization in Example 1, its performance is also significantly reduced, especially the thermal insulation performance and ductility are significantly reduced. Combined with the test results of Comparative Example 2, when the polyimide aerogel composite acrylate resin is directly replaced with acrylic resin in equal amounts, its thermal insulation performance, ductility and mechanical properties are significantly reduced. Combined with the test results of Comparative Example 3, when acrylate resin is directly used for modification without adding polyimide aerogel, its comprehensive performance is slightly improved compared with Comparative Example 2, but it is still far weaker than Example 1. Combined with the test results of Comparative Example 4, when PVA fiber is modified only with epoxy resin, its performance is significantly reduced.

[0138] Combined with the test results of Example 1 and Comparative Example 5, when the modified PVA fiber is not added, it may be the expanded perlite added in the raw materials that makes the strength of the cement mortar lower, and its ductility and thermal insulation properties are also reduced. Combined with the test results of Comparative Example 6, its strength is significantly reduced when calcium silicate is not added.

[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high ductility cement-based composite material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 90-120 parts of cement, 50-60 parts of water, 0.3-0.8 parts of admixture, 5-10 parts of PE fiber, 5-10 parts of modified PVA fiber, 50-70 parts of sand, 8-15 parts of hollow glass microspheres, 10-20 parts of silica fume, 10-20 parts of calcium silicate, and 10-15 parts of expanded perlite; The modified PVA fiber is prepared by composite modification of polyimide aerogel, acrylate resin and epoxy resin.

2. A high ductility cement-based composite material according to claim 1, characterized in that: The modified PVA fiber is prepared by the following method: PVA fiber is mixed and dispersed with a mixed solution of water and acetone, then a polyimide aerogel composite acrylate resin is added and stirred and dispersed, ammonia water and sodium stearate are added and the temperature is raised to 45-55° C., then epoxy resin is added and stirred for 30-40 minutes, and then dried after cooling to obtain a dried product, and then the dried product is ultrasonically dispersed in a hydroxypropyl beta-cyclodextrin solution and centrifugally dried to remove water to obtain the modified PVA fiber.

3. A high ductility cement-based composite material according to claim 2, characterized in that: During the preparation of the modified PVA fiber, each raw material is added according to the following weight portions: 15-20 parts of PVA fiber, 10-20 parts of water, 10-20 parts of acetone, 5-10 parts of polyimide aerogel composite acrylate resin, 3-5 parts of ammonia water, 0.5-1 part of sodium stearate, and 3-6 parts of epoxy resin; and the amount of hydroxypropyl β-cyclodextrin solution added is 3-5 times the mass of the dried product, and the mass concentration of the hydroxypropyl β-cyclodextrin solution is 35-50wt%.

4. A high ductility cement-based composite material according to claim 2, characterized in that: The polyimide aerogel composite acrylate resin is prepared by the following method: 1) adding (1 / 4-1 / 2) of the total amount of acrylate monomers, mixing with sodium styrene sulfonate and solvent A, adding polyimide aerogel, impregnating and drying to obtain pretreated aerogel; 2) mixing the remaining acrylate monomers, dimethylaminoethyl acrylate, 2-acrylamide-2-methylpropane sulfonic acid, propylene glycol monoallyl ether, initiator, crosslinking agent and stabilizer, toluene and solvent B to obtain a reaction solution, then adding the pretreated aerogel prepared in step 1), polymerizing at 80-90° C. for 3-5 hours, then heating to 110-120° C. for reaction for 1-2 hours to obtain a polyimide aerogel composite acrylate resin.

5. A high ductility cement-based composite material according to claim 4, characterized in that: The acrylate monomer is selected from one or more of methyl methacrylate, ethyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, and lauryl methacrylate; the initiator is selected from one or both of benzoyl peroxide and azobisisobutyronitrile; the crosslinking agent is selected from one or both of ethylene glycol dimethacrylate and trimethylolpropane triacrylate; the stabilizer is selected from one or more of polyvinyl pyrrolidone and polyethylene glycol; the solvent A in step 1) is selected from methanol and water in a mass ratio of 1: (1.2-1.3); the solvent B in step 2) is selected from a mixture of water and sodium dodecyl sulfate in a mass ratio of 1: (0.1-0.2).

6. A high ductility cement-based composite material according to claim 5, characterized in that: When preparing the polyimide aerogel composite acrylate resin, the raw materials are added according to the following weight parts: 30-50 parts of acrylate monomer, 5-8 parts of sodium styrene sulfonate, 40-50 parts of solvent A, 20-30 parts of polyimide aerogel, 10-20 parts of dimethylaminoethyl acrylate, 8-15 parts of 2-acrylamide-2-methylpropane sulfonic acid, 10-20 parts of propylene glycol monoallyl ether, 3-5 parts of initiator, 3-5 parts of crosslinking agent, 3-5 parts of stabilizer, 3-5 parts of toluene, and 60-70 parts of solvent B.

7. The high ductility cement-based composite material according to claim 1, characterized in that: The PE fiber is added after the following pretreatment: 1) melting and blending silica gel particles and EPDM rubber particles, adding dioctyl phthalate and mixing them to obtain a blend; 2) melting the PE fiber, mixing it with the blend obtained in step 1) and nano-carbon tubes and performing composite spinning to obtain pretreated PE fiber and then adding it.

8. A high ductility cement-based composite material according to claim 7, characterized in that: During the pretreatment of the PE fiber, the mass ratio of silica gel particles to EPDM rubber is 1: (2-3), the amount of dioctyl phthalate added is 1-3wt% of the silica gel particles, the mass ratio of PE fiber to the blend is 1: (0.1-0.2), and the amount of carbon nanotubes added is 1-3wt% of the PE fiber.

9. The high ductility cement-based composite material according to claim 7, characterized in that: The length of the pretreated PE fibers was 5-10 mm and the diameter was 30-40 μm.

10. A method for preparing a high-ductility cement-based composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Cement, silica fume, sand, hollow glass microspheres, calcium silicate and expanded perlite are mixed and then PE fiber is added to obtain a dry-mixed mixture; the admixture is mixed with water to obtain a mixture, and then modified PVA fiber is added, stirred evenly, and then added to the dry-mixed mixture, and stirred evenly to obtain an energy-saving, heat-insulating and highly ductile cement-based composite material.

Citation Information

Patent Citations

  • Cement-based composite material with high strength, high ductility, and high water resistance and preparation method of cement-based composite material

    CN107382180A

  • Protective film with antibacterial function

    CN111440516A